Formulation and Characterization of Tretinoin Nanostructured Lipid Carriers Using Apifil and Cremophore - Jafar, Garnadi; Putriyanti, Al-fira; Muhsinin, Soni (Universitas Padjadjaran (Unpad), 2023)
The most widely used vitamin A derivative for mild to severe acne is tretinoin. However, it is lipophilic (LogP 6.3). Tretinoin must be transformed into liquid lipids and NLC (nanostructured lipid carriers) based on Apifil® and stabilized by surfactants to address permeability and stability concerns. Heat homogenization and sonication with a sonicator probe were used to formulate tretinoin into NLC. Apifil®, Myritol®, and Chremophore® RH 40 were the materials utilized. Particle size, polydispersity index, zeta potential, adsorption effectiveness, and morphological measurements were then used to describe NLC. The characterization results showed that NLC tretinoin has a particle size of <200 nm for 2 measurements over 30 days, a polydispersity index value of 0.5, a zeta potential range of -7 mV to -19.3 mV, and an efficiency entrapment value of >80% for all formulas. Spherical shape emerged from the morphology data. Conclusion: The findings demonstrate that tretinoin's nanostructured lipid carriers provide favorable characterization outcomes. Keywords: Diabetes, Metformin HCl, Extended release, Direct compressed, Hypromellose, Carboxymethylcellulose natrium.